Pengembangan Board Game Edukasi Dengan Teknologi Augmented Reality (Studi Kasus Permainan Ular Tangga) - Mikhanael Mual Parsaulian Simanjuntak; Tri Afirianto; Wibisono Sukmo Wardhono (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
In the phase of children at the age of 4 to 8 or can be said to be the golden age phase where they begin to understand everything in the environment around them, so there is a need for good direction in education in reading and calculating as in mathematics. Educational games are one form of game that brings elements of learning into the game. The interactivity as child in playing is also important to attract the interest of children in playing while learning. The game designed in this study uses the Iterative Rapid Paper Prototype method, which is used to found out the fun elements, attract children to learn and play, and get good experience in testing the interactivity of Augmented Reality that is delivered in the game. The development of the game Snakes and Ladders with AR technology, which is to attract the interest of learning children has become one of the goals in this research. Influence within the game are shown by the results of tests that carried out through fun testing, pre-testing, and post-testing. After the correspondent plays the Snakes and Ladders Counting shows that the results that make children's interest in learning mathematics increase. The results obtained in the pre-test with an average of 72 shown increased compared to the post-test results which got an average of 92. The results of the fun testing test were obtained from the answers for each question and most 80% of the correspondent shown satisfied with the game Snakes and Ladders Counting.